Issues on the Electron Stopping Power Modulated by Magnetic and Electric Fields - Matheus Corrêa Dantas Avelar; Tarcisio Passos Ribeiro Campos; Túlio Henrique Lopes Gomes de Castro; Paulo Sérgio Soares Guimarães (Brazilian Journal of Radiation Sciences, 2021)
Ionizing radiation has been employed in conjunction with various clinical modalities for therapeutic purposes. Often, surgery, chemo and radiation therapies have been combined on the arsenal against cancer. Nontraditional techniques, as Tumor Treating Fields (TTF) that uses low-intensity variable electric fields, have also been employed for the treatment of brain tumors, glioblastoma multiforme (GBM), with promising results in reducing the harmful radio and chemotherapy effects, while maintaining the same tumor control rates. The combination of electromagnetic field and chemotherapy has already held a clinical investigation; however, it is missing the experimental and theoretical studies coupling electric and magnetic fields with electron radiotherapy. Herein, a theoretical analysis involving the Stopping Power of electron particles in conjunction with static electric and magnetic fields (E, H) was addressed in order to study the relevance of the use of external electromagnetic fields in radiotherapy. The findings reinforce the possibility of application of the coupling magnetic field with electron radiotherapy, and open a horizon to future experimental and clinical studies if the relevance is enough.